Experiential and Joyful Learning-Marine Edutourism (Ejoy-Me) Based on Kuala Selangor Nature Park Potential to Improve Environmental Literacy - RIZA SATIVANI HAYATI; AINUN JARIAH; JULIA ASTUTIK; MUHAMMAD WAJDI; RAHMATIA THAHIR (International Journal of Multidisciplinary Research and Studies, 2023)
Kuala Selangor Nature Park has the potential to be packaged as a learning resource to increase environmental literacy through the Experiential and Joyfull Learning-Marine Edutourism (EJoy-ME) learning model. The purpose of this activity is to implement EJoy-ME for Kuala Lumpur Indonesian School students to increase environmental literacy. Activities focused on the open mind EJoy-ME model for SIKL teachers, developing learning tools based on the potential of the Kuala Selangor Nature Park mangrove ecosystem, and implementing EJoy-ME according to the syntax. The implementation of EJoy-ME has proven to be able to increase the environmental literacy of Kuala Lumpur Indonesian School students. This also gets a positive response from students, namely providing environmental material satisfaction, location selection, satisfaction of the learning process.